Do I need to be positive to be happy? Considering the role of self-esteem, life satisfaction, and psychological distress in portuguese adolescents' subjective happiness - Freire, Teresa (2020)
This study aims to analyze the relationships between gender, age, positive (self-esteem, life satisfaction) and negative/distress psychological variables (anxiety, depression, stress), and subjective happiness. A total of 910 adolescents (51.0% girls, mean age of 13.89 years) answered measures of subjective happiness, life satisfaction, self-esteem, depression, anxiety, and stress. Girls showed lower life satisfaction and self-esteem and greater distress symptoms than boys. Older age was associated with lower subjective happiness, life satisfaction, and self-esteem and greater distress symptoms. Being girl, younger, having lower levels of depressive symptoms, and higher levels of life satisfaction and self-esteem were associated with greater subjective happiness. Self-esteem was a moderator between depressive symptoms and subjective happiness, and stress and subjective happiness. Life satisfaction was a moderator between depression and subjective happiness. Results highlight the role of life satisfaction and self-esteem as a positive functioning dimension for adolescents to manage, regulate, or minimize their psychological distress and to build higher levels of subjective happiness as a source of positive mental health.